FAKTOR-FAKTOR KONSUMSI YANG BERHUBUNGAN DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Pangestu, Bagas Abdi; Wati, Desti Ambar; Khairan, Masayu Dian; Akhrian, Mayesti (POLTEKKES KEMENKES MANADO, 2025)
Hypertension, or high blood pressure, is one of the most prevalent non-communicable diseases in Indonesia. The Indonesian Health Survey (SKI) in 2023 reported that the prevalence of hypertension based on measurements in individuals aged ≥18 years was 30.8%. This study aimed to identify consumption factors associated with blood pressure in hypertensive patients at the Internal Medicine Clinic of Batin Mangunang Regional Hospital of Tanggamus Regency in 2024. This quantitative study employed an analytical survey with a cross-sectional design. The population consisted of 42 hypertensive patients visiting the Internal Medicine Clinic in October 2024, selected through accidental sampling. The independent variables were fruit consumption patterns, drinking water consumption patterns, and coffee consumption patterns, while the dependent variable was blood pressure. Data were collected using the Food Frequency Questionnaire (FFQ). The results showed no significant relationship between fruit consumption patterns and systolic (p = 0.820) or diastolic blood pressure (p = 0.676). Similarly, no significant relationships were found for drinking water consumption (systolic p = 0.289; diastolic p = 0.753) or coffee consumption patterns (systolic p = 0.899; diastolic p = 0.874). Conclusion It was concluded that fruit consumption, drinking water, and coffee consumption patterns were not associated with blood pressure in the respondents.